Studi Awal Pengembangan Tumbuhan Obat-Obatan Sebagai Destinasi Wisata Kesehatan Berbasis Biodiversitas Di Desa Karang Sidemen, Nusa Tenggara Barat - Hayati; valentino, niechi; Setiawan, Budhy; Webliana, Kornelia; Prasetyo, Andrie Ridzki; Gozali, M. Rijalul; Hadi , Muhammad Anwar; Syahruanda, Eggi (Jurnal Pengabdian Magister Pendidikan IPA, 2024)
Karang Sidemen Village plays an important role in protecting and preserving the rich biodiversity around the Mount Rinjani area, especially in the use of medicinal plants as an inseparable part of the "Gumi Sasak" cultural heritage. This service aims to document the potential of medicinal plants along the tourist route through the creation of distribution maps and plant pocket books. This service is carried out using the Community Based Participatory Research (CBPR) method which includes steps such as: initial coordination, socialization, exploration, data analysis, and submission of service results. The result of this service was that 82 families, 253 genera and 303 species were obtained with a total number of plant individuals found along the Karang Sidemen village tourist route of 8,139 individuals, of which 25 plant species were selected for making a draft pocket book and at the same time making a distribution map into a 2D map.